Targeting GDF15 to enhance immunotherapy efficacy in glioblastoma through tumor microenvironment-responsive CRISPR-Cas9 nanoparticles - Cheng Zou; Xiao Liu; Weizhong Wang; Lei He; Anan Yin; Zhengcong Cao; Maorong Zhu; Yuxin Wu; Xiaolin Liu; Jiying Ma; Yalong He; Shuning Wang; et al. (Journal of Nanobiotechnology)
Abstract Despite the outstanding clinical success of immunotherapy, its therapeutic efficacy in glioblastoma (GBM) is still limited. To identify critical regulators of GBM immunity, we constructed a mouse single-guide RNA (sgRNA) library corresponding to all disease-related immune genes, and performed an in vivo CRISPR knockout (KO) screen in syngeneic GBM mouse models. We demonstrated that the deletion of GDF15 in GBM cells ameliorated the immunosuppressive tumor microenvironment (TME) and enhanced the antitumor efficacy of immune checkpoint blockade (ICB) response. Moreover, we designed unique nanoparticles for efficient encapsulation of CRISPR-Cas9, noninvasive brain delivery and tumor cell targeting, demonstrating an effective and safe strategy for GDF15 gene therapy. The CRISPR-Cas9 nanoparticles, known as ANPSS (Cas9/sgRNA), are easily created by enclosing a single Cas9/sgRNA complex in a polymer shell that is sensitive to glutathione. This shell also contains a dual-action ligand that aids in crossing the blood‒brain barrier, targeting tumor cells, and selectively releasing Cas9/sgRNA. Our encapsulating nanoparticles demonstrated promising GBM targeting, resulting in high GDF15 gene editing efficiency within brain tumors while showing minimal off-target gene editing in high-risk tissues. Treatment with ANPSS (Cas9/sgGDF15) effectively halted tumor growth, reversed immune suppression, and enhanced the efficacy of ICB therapy. These results emphasize the potential role of GDF15 in modulating the immune microenvironment and enhancing the effectiveness of current immunotherapy strategies for GBM. Graphical Abstract